MAPPING OF SAND MINING AREAS USING REMOTE SENSING AND GIS: A CASE STUDY IN PARTS OF SWARNAMUKHI RIVER BED, CHITTOOR DISTRICT, ANDHRA PRADESH - B.MURALIDHARA REDDY; SRAVYA SAI GUDDETI; K. NAGAMANI (The Bioscan, 2021)
Sand is an important source engineering material and it is mainly used for construction works which is obtained from a large rock material, due to the action of different geological agents the sand is formed nearby the course of the river. In recent times there is an extensive pressure on rivers which acts as a treasure for the building sector due to rapid growth in the development activities. The main objective of the study is to investigate, recognize the areal extent of sand mining areas of Swarnamukhi River, a total of 9 major sites were identified and demarcated in parts of Srikalahasthi and Thotambedu Mandals of Chittoor District, Andhra Pradesh, by using Google earth and Arc GIS 10.4. This study is an attempt to know the utility of Google earth, Remote Sensing and GIS software tools in the field of natural resource monitoring and environmental protection. The study results areal extent concludes that there is overexploitation of sand from Thotambedu Mandal as it is near to road sites when compared to Srikalahasthi Mandal. This overexploitation of sand leads to river discharge.